2007
DOI: 10.1186/1471-2431-7-28
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccination coverage: findings from immunization information systems

Abstract: BackgroundBeginning with the 2004–05 influenza season, the Advisory Committee on Immunization Practices (ACIP) strengthened their existing encouragement that children aged 6–23 months receive influenza vaccination by creating a formal recommendation.MethodsWell-functioning sentinel project immunization information systems (IIS) in Arizona (AIIS) and Michigan (MIIS) were used to calculate vaccination coverage among children aged 6–23 months during the 2004–05 influenza season. We calculated 2 measures of vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Vaccination registries have been shown to be useful in clinical assessment and in estimating coverage [12]. In Navarre, the vaccine register is used primarily so that physicians and nurses can consult the vaccine status of their patients at any time and to programme the dates to administer the doses of the vaccine schedule.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination registries have been shown to be useful in clinical assessment and in estimating coverage [12]. In Navarre, the vaccine register is used primarily so that physicians and nurses can consult the vaccine status of their patients at any time and to programme the dates to administer the doses of the vaccine schedule.…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining the quality of data in IISs have shown that these data are often incomplete and inaccurate [16][17][18]. Other documented issues are timeliness of reporting [19,20] and coverage, or the percentage of children in a population with a record in an IIS [19,21].…”
Section: Immunization Information Systemsmentioning
confidence: 99%
“…IISs collect and consolidate records of vaccinations from multiple health care providers and across care settings. These surveillance systems have been shown to provide better immunization delivery by assisting in medical decision-making, reminder recall, determining coverage levels, and identifying pockets of need [10][11][12][13][14][15]. IISs can be used in VE studies to measure the degree of vaccine uptake in a variety of settings and populations by identifying confirmed VPD cases and/or confirming immunization history.…”
Section: Introductionmentioning
confidence: 99%